CRISPR/Cas9 mutagenesis abolishes odorant-binding protein BdorOBP56f-2 and impairs the perception of methyl eugenol in Bactrocera dorsalis (Hendel). (December 2021) - Chen, Xiaofeng; Lei, Yibo; Li, Hongfei; Xu, Li; Yang, Hui; Wang, Jinjun; Jiang, Hongbo
Abstract: Olfaction underpins many insect behaviors, such as foraging, host location, mating, and predator avoidance. In the first step of insect olfaction, odorant-binding proteins (OBPs) bind hydrophobic odorants and transport them to odorant receptors. Methyl eugenol (ME) is a powerful attractant for mature males of the oriental fruit fly Bactrocera dorsalis (Hendel), one of the most destructive fruit pests. The underlying molecular mechanism is unclear, but there is in vitro evidence that BdorOBP56f-2 is involved in ME perception. We used microscale thermophoresis to confirm that BdorOBP56f-2 directly binds ME with strong affinity i n vitro . We then used CRISPR/Cas9 to knock out the BdorOBP56f-2 gene, allowing us to establish a homozygous mutant B. dorsalis line. The electroantennogram response and behavioral attraction to ME were significantly reduced in the mutant, providing in vivo evidence that BdorOBP56f-2 is necessary for efficient ME perception. Our results offer insight into the molecular mechanism of ME perception in B. dorsalis and provide a theoretical basis for the functional analysis of other OBPs. Graphical abstract: Image 1 Highlights: BdorOBP56f-2 has strong direct binding affinity to ME using microscale thermophoresis assay in vitro. The BdorOBP56f-2 −/− mutants were generated by the CRISPR/Cas9 system mediated mutagenesis. The mutants showed significantly decreased electroantennogram response and behavioral attraction to methyl eugenol.